Le système Amazon aux États-Unis face aux crises : miroir du système de transport et de logistique des États-Unis - Matthieu Schorung (Bulletin de l’Association de Géographes Français)
The United States, the world’s leading economic power and second-largest trading power, enjoys considerable advantages in the globalization process, including the strength of its transportation system and its strategic positioning in global supply and distribution chains. The U.S. territory is open to globalization via its dynamic maritime façades (Pacific, Northeast, Gulf of Mexico and Great Lakes). Huge logistics platforms, often multimodal, have been developed around these interfaces, the recent pandemic has further strengthened them. The balances (port and airport hierarchies, for example) that are taking shape at the start of 2023 bear witness to the fairly limited structural effects of this succession of crises since 2020. The Amazon case study bears witness to this "logistics turnaround" in the US economy, and to the resilience of the US transportation system.